Proposição de uma ferramenta para medir a maturidade de digitalização de portos - Bilcati, Tatiane (2023)
Ports, as part of the global supply chain, have been affected by digital transformations in their production processes, and must be able to adapt efficiently, minimizing unproductive operations. In this context, the objective of this work is to develop a tool to measure the maturity level of port digitalization, categorized into three application perspectives: logistics, operations and planning and management. To this end, a systematic literature review was developed using the MethodiOrdinatio methodology, with these analyzes being important for the construction of a theoretical model for analyzing digitalization maturity in ports. From the literature review, it was defined where and what technologies are most used in ports. From this, a maturity research tool was developed, which was validated by port sector experts and subsequently applied to a reference port in the southern region. As a result, the tool was validated and improved by experts, and its application proved to be adequate and efficient. The analyzed port was classified as maturity level 1, presenting greater maturity from an operations perspective, highlighting the use of technologies in the port's maintenance processes, as well as the technologies fully implemented were cybersecurity and integration with emphasis on in gate management, maintenance, scheduling and traffic control systems.